ANALISIS DAMPAK STRES AKADEMIK MAHASISWA DALAM PENYELESAIAN TUGAS AKHIR ( SKRIPSI ) ( STUDI PADA MAHASISWA PROGRAM STUDI MANAJEMEN UIN SULTAN SYARIF KASIM RIAU DAN UNIVERISTAS INTERNASIONAL BATAM KEPULAUAN RIAU ) - Mulia Sosiady; Ermansyah Ermansyah (Jurnal EL-RIYASAH, 2020)
This research is located in the Management Study Program located in Pekanbaru and the Management Study Program Batam International University. The research began in June to December 2017, this research is motivated that students experience stress as demands of academic life that must be undertaken, including activities outside academic activities including socializing and adjust to fellow students who have different characteristics and backgrounds, these conditions become stressors for students when completing the final project / thesis. The conclusion in this study from the Analysis of Researchers Internal Factors which tends to cause Academic Stress Management Study Program UIN Sultan Syarif Kasim Riau and Batam International University Management Study Program namely Internal Factors such as: Ability and Intelligence are not well developed such as Visual Ability, Verbal Ability and Ability Numerical and Conceptual Ability While External Factors which tend to cause Academic Stress Students of Management Study Program of UIN Sultan Syarif Kasim Riau and Batam International University Management Study Program, namely External Factors such as: Procedure System for submission of Thesis Title Proposals is considered difficult for students because they have to pass the Originality and Majority Study Program of Syarif Kasim Riau Study Program and Batam International University Management Study Program. Student Work. Suggestions Students should apply "Problem focused coping" more focused on solving the problem, Students should be able to Emotion-focused coping more focused on controlling emotional responses, Of course the most important thing is to increase Spiritual Questions (Faith and Taqwa) To Allah SWT.